Effects of Intra-vitreal Injection of Bevacizumab as an Adjunct during Phacoemulsification in Diabetic Maculopathy: Doi: 10.36351/pjo.v37i1.1122 - Bodla, Ali Afzal; Minahil Kazmi, Syeda; Tariq, Noor; Moazzam, Ayema; Muneeb Aman, Muhammad (Pakistan Journal of Ophthalmology, 2020)
Purpose: To study the effects of Intra-vitreal injection of Bevacizumab as an adjunct during phacoemulsification in patients with diabetic retinopathy. Study Design: Quasi experimental study. Methods: Hundred diabetic patients who were scheduled to undergo phacoemulsification were included in the study. They were equally divided into two groups; Bevacizumab and control group. Complete ocular examination and macular thickness and volume were determined using an OPTOVUE-OCT machine. The patients in the Bevacizumab group were given intra-vitreal injection of 1.25 mg/0.05ml of Bevacizumab at the time of Phacoemulsification. A written ethical approval was obtained and the study was conducted according to principles of declaration of Helsinki. Results: The bevacizumab group manifested low value of CMT one month post-surgery as compared to the control group (262.2 ± 32.2 and 288.5 ± 54.1, respectively) with P = 0.01. The Total Macular volume, and Best-corrected visual acuity in the two groups showed no significant difference one month after surgery. Amongst the patients who developed postsurgical macular edema, four patients did not possess a positive history for diabetic retinopathy and 3 of them had Non Proliferative Diabetic Retinopathy. We found no significant relationship between the post-surgical macula edema with the presence of mild Non Proliferative Diabetic Retinopathy. (Fisher’s test, P = 0.321). Conclusion: The ocular anti-VEGF therapy substantially reduces macular edema secondary to post-surgical inflammation in diabetic patients. It effectively reduces the central macular thickness although the results are not found to be statistically significant when compared with the control group. Key Words: Diabetes mellitus; diabetic macular edema; diabetic retinopathy: Bevacizumab.